Development Of Smartphone Based Physiotherapy Service Applications - Pristianto, Arif; Susilo, Taufik Eko; Faizah, Zulfa Nur; Aranti, Wulan Adis; Rifandi, Reza Aristo (SEAN Institute, 2024)
The role of communication technology between individuals is increasingly developing and has various ways and methods. One of the health services is physiotherapy which provides the latest innovations such as the emergence of the term telephysio. Telephysio is the development of a remote monitoring system to facilitate independent rehabilitation of patients in their own homes. The large number of people using smartphones has made the development of applications increasingly sophisticated, especially applications in the health sector. Objective of this research is to make physiotherapy services easier for users with applications on smartphones. This research model was carried out using the R&D (Research and Development) method which was carried out up to the trial and application function testing stages. the application was assessed by two experts in the field of technology and physiotherapy services. Test results show that the existing features and menus provide ease of use and effectiveness in helping patients find and obtain physiotherapy services. Based on the results that have been carried out by expert judgment and trials of smartphone-based physiotherapy service applications, it has been found that the application can be used and is quite suitable for use according to its function, although there are still many shortcomings and things that need to be considered for further development and research